Sistem bantuan pemilihan ke Institut Pendidikan Tinggi Awam (IPTA) - Abd. Rahim, Yahaya (2001)
The issue of placement students in IPTA is being widely discussed in our country recently. According to Ministry of Education, every year about 30% to 40% application was rejected due to several reasons. Among the reasons are the course applied is not parallel to their academic qualification or in another terms, their academic qualification does not met with the required qualification for that course. Due to that, the varsity had to reject their application or offered them another course that is relevant to their qualification. What was being argued here is that does the applicant understood the condition required for the course or the applicant does not have sufficient information on courses offered in the varsity or PTA ?. Thus they choose a course with regards to their interest rather than looking at the required qualification. In cases happens to those who have a qualification that is almost the same as all the courses qualification in the IPTA. Decision Support System technology is a very important technology in helping the public making a decision. This system is developed to help a targeted group in making a sound, wise and efficient decision. The decision support systems that were develop for public group and in a form of multimedia are relatively small in the market especially if the system is being developed using Internet as its platform. Based on this scenario, therefore this system has been suggested to fill in that gap. Decision support system was suggested as the best solution for catering this problem. This system is predicted to be user fiend& and helpful to applicant in order to determine a suitable course for the user with accordance to their qualification